2002
DOI: 10.1086/342060
|View full text |Cite
|
Sign up to set email alerts
|

Trichomonas vaginalisPolymerase Chain Reaction Compared with Standard Diagnostic and Therapeutic Protocols for Detection and Treatment of Vaginal Trichomoniasis

Abstract: Wet preparation has limited sensitivity for diagnosis of Trichomonas vaginalis (TV) infection. An observational study of 337 women was conducted to evaluate a new polymerase chain reaction (PCR) test for TV. The sensitivities of wet preparation and TV culture were 52% (95% confidence interval [CI], 41-62) and 78% (95% CI, 69-86), respectively. TV PCR had a sensitivity of 84% (95% CI, 75-90) and a specificity of 94% (95% CI, 90-97). Metronidazole was provided to 67 (69%) of 97 women with TV because of TV on wet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
72
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(83 citation statements)
references
References 14 publications
9
72
0
2
Order By: Relevance
“…Infection would have been missed in 32% if only microscopy was performed. The sensitivity and specificity of microscopy in our study is comparable with other studies [5][6][7][8]. The manufacturer states 83% sensitivity and 99% specificity of ICT compared to 'culture and PCR combination' and 96% sensitivity and 95% specificity compared to wet mount.…”
Section: Discussionsupporting
confidence: 88%
“…Infection would have been missed in 32% if only microscopy was performed. The sensitivity and specificity of microscopy in our study is comparable with other studies [5][6][7][8]. The manufacturer states 83% sensitivity and 99% specificity of ICT compared to 'culture and PCR combination' and 96% sensitivity and 95% specificity compared to wet mount.…”
Section: Discussionsupporting
confidence: 88%
“…Ignoring the latter issue yet another problem arises. Diagnosis of cases investigated from clinical suspicion of trichomoniasis are at mercy of low sensitivity of current diagnostic standards as recent evaluations over the past decade have come to find (Lusk et al, 2010;Roth et al, 2011;Seña et al, 2007;Van Der Pol, 2007;Wendel et al, 2002). The most prevalent and most promising techniques will be reviewed below while a more detailed overview of guidelines for laboratory diagnosis and the methodology can be found in Domeika et al (2010).…”
Section: Diagnosismentioning
confidence: 99%
“…Additionally, this method is expensive and time consuming (Domeika et al, 2010) despite the availability of commercial culture systems (InPouch TV system: BioMed Diagnostics). Studies have found sensitivities ranging between 75-83% and specificity near 100% (Huppert et al, 2007;Nye et al, 2009;Wendel et al, 2002). Wet mount is an attractive diagnostic tool due to its simplicity and cost effectiveness, and is consequently the most widely used (Huppert et al, 2007).…”
Section: Culture and Wet Mount Microscopymentioning
confidence: 99%
See 2 more Smart Citations